Assessing the Impact of SSRIS (e.g., Sertraline) on Postpartum Depression Outcomes - Amjad Ali, Humaira Rahim, Shafiullah, Imran Saeed, Ashfaq Hussain, Muhammad Iqbal Qasim (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Postpartum depression (PPD) is a common mental health issue affecting new mothers with ramifications for both the mother’s welfare and child development. SSRIs, such as sertraline, are often used to treat PPD. The purpose of this study was to evaluate the effectiveness and safety of SSRIs, especially sertraline for treatment response in PPD patients. Methods: One hundred and fifty patients diagnosed with PPD participated in a 12-week open-label trial of sertraline (50-200 mg/day). The primary efficacy endpoints were change in EPDS and HDRS scores from baseline to weeks 6 and 12. Secondary endpoints were adverseevents and medication compliance. Results: EPDS scores at 12 weeks had significantly decreased compared to those at baseline (p < 0.001). The average decrease in EPDS-PPS score was 15 points, representing significant relief from depressive complaints. The increase in HDRS scores was equally significant (p < 0.001). No serious adverse events were reported, though mild side effects such as nausea and headaches were common. Conclusion: SSRIs, and in particular sertraline, were efficacious for postpartum depression with the most marked reduction in severity occurring within 12 weeks. Side effects were tolerable for most patients and were mild in the majority. Keywords: Postpartum depression, sertraline, SSRIs, outcomes of treatment, adherence to medication.